Brand positioning through distribution channels - Moreno-Zuñiga, Jorge Eliecer
The following review article shows the changing dynamics of interaction between brands and consumers. It shows how companies compare their different points of view in relation to what is the best way to reach their customers or stakeholders, under a constant evolution of the market, the media of attraction and the digital era. Another relevant aspect explored is the influence of the different contact channels that emerged after the pandemic and the constant change and influence on marketing, awakening the need to create mixed distribution strategies oriented to dynamically change so that companies do not disappear in time.